Estrategias competitivas y gestión deportiva: una perspectiva de la Teoría Basada en Recursos aplicada al sector del fútbol - Quispe, Julio (2018)
Purpose – This research uses the Resource-based Theory as the basis for a model that allows integrating organizational actions with the variables that can moderate directly or indirectly their impact on the high performance of football clubs. Design/methodology/focus – An empirical test was developed in three phases. The first was the linear regression technique. Second a multivariate analysis of covariance (MANCOVA) and the third procedure a regression by least squares in two phases. The objective of using these last two procedures was to evaluate the joint effect of the independent variables on the dependent variables as well as the effects of interaction between them. Findings – The direct and indirect relationships between the organizational and decisional variables foreseen in the model are validated. It also validates the importance of promotional actions of the club to achieve competitiveness based on its performance or results. Limitations/implications – Future research could be replicated in other countries using larger samples with more complex statistical techniques. Also it could be tested if the relationships found can vary according to the cultures or other variables not contemplated in this study can be used. Practical implications – The questionnaire used is a reliable source of information for marketing managers of football clubs since the scales can be used as guides to assess and diagnose their performance-based competitiveness potential. Social implications – Football clubs have a direct development and impact on society. Therefore the implications in the club will fall on the immediate environment (fans and society). Originality/value – This research provides several fundamental contributions to the literature on organizational competitiveness in the sports sector with specific application to football clubs. This is one of the few studies that show that competitiveness is the result of motivational and organizational dynamics and that the success of clubs is based on a more complex phenomenon than just attendance at events. Also it is an investigation in an emerging country which extends the theoretical and practical applicability of the phenomenon studied.